The Impact of Climate Change on Cardiovascular Problems of the Elderly in Agricultural Areas - Decky Vrista Tri Anggoro; Tantut Susanto; Fahruddin Kurdi (Al-Hijrah Indonesia, 2026)
Exposure to extreme temperatures and air pollution in the agricultural sector causes cardiovascular problems in the elderly. The aging process in the agricultural sector is also correlated with hypertension problems, because the aging process also changes the cardiovascular system and is related to the incidence of hypertension. Furthermore, climate change is also related to hypertension problems or cardiovascular disorders in the elderly. Therefore, it is necessary to analyze the impact of climate change on cardiovascular disease among the elderly to ensure their quality of life in the agricultural sector. Based on the explanation above, it can be concluded that climate change has a significant impact on the health problems of the elderly in the agronursing system. Climate change, including exposure to extreme heat and air pollution, affects cardiovascular disorders among elderly farmers. In responding to these problems, mitigation should be carried out to provide access to health services, enabling farmers, the majority of whom are in developing countries, to minimize the impact of climate change and improve their welfare and quality of life.